Negative pressure pulmonary edema: a case report and literature review - Wu, Jian; Yuan, Hua; Guo, Zhiqiang; Feng, Qiupeng; Ma, Jin (Frontiers in Medicine, 2024)
Negative pressure pulmonary edema (NPPE) is a form of non-cardiogenic pulmonary edema triggered by a swift increase in negative intrapleural pressure due to upper airway obstruction and represents a potential cause of acute respiratory failure.This study documents a case of NPPE post-endotracheal extubation subsequent to general anesthesia. The patient, a young female, underwent a "laparoscopy-assisted unilateral salpingectomy" under general anesthesia for an ectopic pregnancy.Immediately post-extubation, the patient exhibited a sudden decline in oxygen saturation and tachypnea. Pink frothy secretions were suctioned from the oral and nasal cavities. Swift interventions, including oxygen therapy, non-invasive ventilation, diuretics, and corticosteroids, were administered. The patient's condition was effectively managed, and after six days of treatment, she was discharged from the hospital following full recovery.